Technology parks : case studies of successful overseas parks and evaluation of existing and proposed parks in the Cape Metropolitan Region - Bosman, B.(Bisschoff) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. in Town and Regional Planning) -- University of Stellenbosch, 1997.